The Interrelations Of Celebrity Endorsement, Social Media Use, And Customer Engagement In Achieving Customer Purchase Decision - Naila Syalsabila; Nurul Hermina (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – The awareness and massive adoption towards internet has motivated companies to include it into their marketing strategies, such as by using celebrity endorsement and social media use, as this will enable them to increase customer engagement and their purchase decision. Aim – This study investigates the effect of celebrity endorsement and social media use on customer engagement and consumer purchasing decisions. Design / methodology / approach – This research was conducted on consumers of culinary and fashion products of SMEs in West Java Province, with a total sample of 185 respondents. The data was collected using the survey method of distributing questionnaires to respondents. Furthermore, the data obtained were processed using PL S Software-Structural Equation Modeling. Findings – The research results show that: (1) the use of social media has a positive effect on customer engagement; (2) The role of celebrity endorsement has a positive effect on customer engagement; (3) Customer engagement has an impact on purchasing decisions; (4) Customer engagement mediates the relationship between social media use and consumer purchasing decisions, and (5) Customer engagement mediates the relationship between celebrity endorsement and consumer purchasing decisions. Research implication – MSMEs need to understand the important role of the influence of social media in increasing engagement with consumers. The use of celebrity endorsement must also be considered as an important aspect that can encourage consumer engagement. Limitations – This research was specifically conducted on SMEs in the handicraft and culinary industry in West Java. Future studies require to be carried out in different settings to ensure generalizability of the present study.